2012
DOI: 10.1007/s13277-012-0575-0
|View full text |Cite
|
Sign up to set email alerts
|

TAGLN suppresses proliferation and invasion, and induces apoptosis of colorectal carcinoma cells

Abstract: In order to find the correlation between transgelin gene (TAGLN) and colorectal carcinoma occurrence, we investigated the expression of TAGLN in colorectal carcinoma tissue samples and colorectal carcinoma LoVo cells. Meanwhile, the effects of TAGLN on the characteristics of LoVo cells were also examined. The expressions of TAGLN in colorectal carcinoma tissues, adjacent normal tissues, and LoVo cells were detected by the Western blot method. The recombinant plasmid pcDNA3.1-TAGLN was established and transfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…our observation of a decreased expression of transgelin in the leiomyoma compared to normal myometrium is in agreement with that of other studies (38). li et al found a reduction of the protein in colorectal cancer cell lines, as transgelin suppresses proliferation and invasion, and induces apoptosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…our observation of a decreased expression of transgelin in the leiomyoma compared to normal myometrium is in agreement with that of other studies (38). li et al found a reduction of the protein in colorectal cancer cell lines, as transgelin suppresses proliferation and invasion, and induces apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…li et al found a reduction of the protein in colorectal cancer cell lines, as transgelin suppresses proliferation and invasion, and induces apoptosis. The decrease of transgelin promotes cell proliferation, promoting the growth of the leiomyoma (38). Consistent with our present findings, an immunohistochemical study on the myometrium and leiomyoma indicates a higher expression of transgelin in the normal myometrium as compared to leiomyoma tissue sections (39).…”
Section: Discussionsupporting
confidence: 91%
“…[ 17 ] It also impairs tube formation during vasculogenic mimicry in the TNBC cell line, MDA MB 231. [ 16 ] In contrast, restoration of TAGLN expression inhibits the migration of the colorectal cancer cell lines, DLD1, [ 10 ] and LoVo, [ 8 ] and the bladder carcinoma cell line, TSGH‐8301. [ 36 ] Decreases in migration after TAGLN restoration [ 37 ] as well as after TAGLN silencing, [ 18 ] have been described in different studies of SW480 colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al. [ 8 ] observed increased apoptosis in LoVo colorectal carcinoma cells with upregulated TAGLN, while silencing of TAGLN in this cell line leads to a decrease in the number of apoptotic cells. The TAGLN homolog in yeast (Scp 1) regulates the dynamics of the actin cytoskeleton, which influences the release of ROS from mitochondria and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation